An Adaline model predictive control strategy based DSTATCOM for power quality enhancement - Sahu, Gokulananda; Panigrahi, Rakhee; Patjoshi, Rajesh Kumar; Kolluru, Venkata Ratnam (International Journal of Applied Power Engineering (IJAPE), 2024)
This paper represents a least mean square (LMS) built Adaline current estimator in conjunction with model predictive control (MPC) approach (Adaline-MPC) employed for distribution-static-compensator (DSTATCOM) to enrich power quality within power distribution network. The real fundamental frequency components of load currents are estimated via LMS-built Adaline adopting instantaneous weight computation and reference currents are further formed by means of multiplying these weights with unit vector templates. A proportional-integral (PI) controller is engaged in support of continual maintenance of DC-capacitor voltage. Moreover, the switching signals of voltage source converter (VSC) are created via applying MPC wherein source currents should track the reference currents, which is derived from Adaline current estimator. Both MATLAB based simulation and Opal-RT based real-time experimental outcomes are demonstrated and the effectiveness of the proposed Adaline-MPC based DSTATCOM towards power quality improvement has been verified.